Trickle-Down Technology and Screening of a Durable Goods Monopolist - Huang, Su-Chen; Yu, Shih-Ti; Chi, Woody Chih-Yi; Yang, Wen-Ben (Journal of Reviews on Global Economics, 2015)
We show that when it takes time for a durable goods monopolist to make its high-end new technology accessible to low-end market (the trickle-down technology constraint), the monopolist's high-end product might have a higher-than-optimum quality. This result differs from conventional screening models, in which the qualities of non-durable goods supplied by a monopolist never exceed the optimum, and only consumers with the highest valuation consume the efficient quality. In another literature discussing a durable goods monopolist who delays the introduction of low-end product as a marketing strategy, but not due to the trickle-down constraint, the qualities will not exceed the optimum either. Our results show that the trickle-down constraint will make the monopolist chooses a higher-than-optimum quality when the difference of the valuations of high demand and low demand consumers are in certain ranges. The intuition follows Spence (1975): the efficient quality is determined by the marginal cost and the average of all consumers' marginal valuations, while the monopolist chooses quality such that the marginal cost equals the marginal consumer's marginal valuation.